Production of first generation adenovirus vectors: a review - Danthinne, X; Imperiale, M J (Gene therapy, 2000)
In the past decade, adenovirus vectors have generated tremendous interest, especially in gene therapy applications. In the so-called 'first generation' adenovirus vectors, the transgenes are inserted in place of the E1 region, or less often the E3 region. Although second-generation and helper-dependent adenovirus vectors will probably prevail in the future in applications that require long-term gene expression, first generation adenovirus vectors will remain very useful in other settings, such as cancer and vaccination, or simply to transfect cell lines that are refractory to other transfection methods. Until a few years ago, the construction of first generation adenovirus vectors was a labor-intensive and time-consuming process. More than 20 methods have appeared that facilitate their construction and are reviewed below.